Dynamical Properties of Rough Group Spaces - Hatef Fahem, Eman; Hameed Hamzah, Sattar (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2024)
Our main aim is introduced some concepts in dynamical system in rough theory . We give the definition of periodic points and critical points and investigate their properties in rough actions . Also, we illustrated the relation between them.